Solution Of Natural Convection Boundary Layer Flow Above A Semi-Infinite Porous Horizontal Plate Under Similarity Transformations With Suction And Blowing (Daffodil International University Journal of Science and Technology, 2011)
In the present study we have confined our attention to the laminar boundary layer equations for the unsteady free convection flow over a heated horizontal semi-infinite porous plate by simplifying them using the Boussinesq approximation. Similarity requirements for an incompressible fluid are sought on the basis of detailed analysis in order to reduce the governing coupled partial differential equations into a set of ordinary differential equations. Numerical results are displayed graphically for some selected values of the controlling parameters provided by the similarity transformation. The influence of suction and blowing on the flow and temperature fields and other flow factors like skin friction and heat transfer coefficients are extensively investigated. It is found that a small value of suction or blowing play a vital role on the patterns of flow and temperature fields as well as on the coefficients of skin friction and heat transfer. Keywords: Natural convection; Boussinesq approximation; Similarity transformation; Suction; blowing. DOI: http://dx.doi.org/10.3329/diujst.v6i1.9333 DIUJST 2011; 6(1): 43-51